2016
DOI: 10.1002/2016gb005458
|View full text |Cite
|
Sign up to set email alerts
|

Modeled Chl:C ratio and derived estimates of phytoplankton carbon biomass and its contribution to total particulate organic carbon in the global surface ocean

Abstract: Chlorophyll (Chl) is a distinctive component of autotrophic organisms, often used as an indicator of phytoplankton biomass in the ocean. However, assessment of phytoplankton biomass from Chl relies on the accurate estimation of the Chl:carbon(C) ratio. Here we present global patterns of Chl:C ratios in the surface ocean obtained from a phytoplankton growth model that accounts for the optimal acclimation of phytoplankton to ambient nutrient, light, and temperature conditions. The model agrees largely with obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
37
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 68 publications
(156 reference statements)
5
37
0
Order By: Relevance
“…On the other hand, in regions dominated by b bp NAP of inorganic nature not covarying with Chl, such as the Southern Ocean, the computation of phytoplankton carbon via b bp exhibits large differences: RPD values greater than 100% (Figure b). The order of magnitude of our phytoplankton carbon biomass is consistent with the recent estimates of phytoplankton carbon by Arteaga et al () computed with a biogeochemical model able to resolve the Chl:C ratio and accounting for the optical acclimation of phytoplankton to nutrient, light, and temperature. A future challenge concerns to take into account the change of the scaling factor relating b bp to C, as reported in Kostadinov et al (, , ), coupled with the b bp NAP spatial variability as found in this work.…”
Section: Resultssupporting
confidence: 90%
“…On the other hand, in regions dominated by b bp NAP of inorganic nature not covarying with Chl, such as the Southern Ocean, the computation of phytoplankton carbon via b bp exhibits large differences: RPD values greater than 100% (Figure b). The order of magnitude of our phytoplankton carbon biomass is consistent with the recent estimates of phytoplankton carbon by Arteaga et al () computed with a biogeochemical model able to resolve the Chl:C ratio and accounting for the optical acclimation of phytoplankton to nutrient, light, and temperature. A future challenge concerns to take into account the change of the scaling factor relating b bp to C, as reported in Kostadinov et al (, , ), coupled with the b bp NAP spatial variability as found in this work.…”
Section: Resultssupporting
confidence: 90%
“…A Chl:C ratio of 0.01 (g g 21 ) also coincides with the Chl:C ratio predicted in oligotrophic, nutrient limited areas of the Atlantic and Pacific oceans (Arteaga et al, 2016;Behrenfeld et al, 2005Behrenfeld et al, , 2016. A relatively low Chl:C ratio in the Southern Ocean suggests a ''break down'' of the photoacclimation mechanism of the cells, which should otherwise induce chlorophyll synthesis (and consequently high Chl:C) as a response to low light levels in this high latitude/deep mixing area (Dong et al, 2008).…”
Section: Inferred Chlorophyllsupporting
confidence: 78%
“…high latitudes, and estuarine and coastal waters, but lower than in less productive regions, e.g. subtropical latitudes and the open ocean (∼30-70%) (Andersson & Rudehäll 1993, Graff et al 2015, Arteaga et al 2016. Daily phytoplanktonic new carbon production (i.e.…”
Section: Contribution Of Total Ph-c and Dipp To Pcmentioning
confidence: 99%